Relevansi Pemikiran Pendidikan Mohammad Hatta Terhadap Pendidikan Islam di Indonesia - Ahmad Syauqi Fuady (Jurnal Pendidikan Islam, 2020)
Mohammad Hatta is very concerned about education, including Islamic education, before and after Indonesian independence. This article aims to explore Mohammad Hatta's educational thoughts about the goals of education, character education, and Indonesian culture, and how they are relevant to Islamic education in Indonesia. This research is a qualitative type with a descriptive-analytical approach. This research model is a library research (library research). The writings of Mohammad Hatta and other relevant authors were used as data sources for study and analysis. Content analysis (content analysis) is used as a data analysis technique. The research results obtained, first the concept of Mohammad Hatta's educational goals is holistic that is relevant to Islamic education. Second, Mohammad Hatta views education that prioritizes character, morals and morals to be the main goal. This is relevant to Islamic education which prioritizes morals. Third, Indonesian culture must be based on religious values, besides being based on science, knowledge and technology. This is relevant to Islamic education which makes religion the foundation of Islamic culture